Fragile X mental retardation protein promotes astrocytoma proliferation via the MEK/ERK signaling pathway - Xing, Zhou (Oncotarget, 2016)
OBJECTIVE: To examine the association between fragile X mental retardation protein (FMRP) expression and astrocytoma characteristics. METHODS: Pathologic grade and expressions of glial fibrillary acidic protein (GFAP), Ki67 (proliferation marker), and FMRP were determined in astrocytoma specimens from 74 patients. Kaplan-Meier survival analysis was undertaken. Pathologic grade and protein levels of FMRP were determined in 24 additional patients with astrocytoma and 6 controls (cerebral trauma). In cultured U251 and U87 cell lines, the effects of FMRP knock-down on cell proliferation, AKT/mTOR/GSK-3β and MEK/ERK signaling were studied. The effects of FMRP knock-down on the volumes and weights of U251 cell-derived orthotopic tumors in mice were investigated. RESULTS: In patients, FMRP expression was increased in grade IV (5.1-fold, P<0.01) and grade III (3.2-fold, P<0.05) astrocytoma, compared with controls. FMRP and Ki67 expressions were positively correlated (R(2)=0.877, P<0.001). Up-regulation of FMRP was associated with poorer survival among patients with FMRP integrated optical density >30 (P<0.01). In astrocytoma cell lines, FMRP knock-down slowed proliferation (P<0.05), inhibited total MEK levels P<0.05, and reduced phosphorylation of MEK (Ser217/221) and ERK (Thr202/Tyr204) (P<0.05). In mice with orthotopic tumors, FMRP knock-down decreased FMRP and Ki67 expressions, and reduced tumor volume and weight (36.3% or 61.5% on day 15, both P<0.01). Also, phosphorylation of MEK (Ser217/221) and ERK (Thr202/Tyr204), and total MEK in xenografts were decreased in sh-FMRP xenografts compared with non-transfected ones (all P<0.05). CONCLUSION: Enhanced FMRP expression in astrocytoma may promote proliferation through activation of MEK/ERK signaling.